Does acute promyelocytic leukemia patient with the STAT5B/RARa fusion gene respond well to decitabine?: A case report and literature review. Issue 43 (23rd October 2020) - Wang, Lei; Yan, Xiaojing; He, Juan
Abstract: Rationale: Most acute promyelocytic leukemia (APL) patients respond to all-trans-retinoic acid (ATRA)and have a good prognosis. However, variants APL who carry PLZF/RARа, STAT5B/RARа, and STAT3/RARа are insensitive to ATRA and have poor prognoses. The standard treatment for variants APL is still unclear due to the small sample size. Patient concerns: Here we reported a Chinese male who was admitted to our hospital with the complaint of rib pain, dyspnea, and fever (37.5°C). Blood tests showed leukopenia (1.83 × 10 9 /L), anemia (hemoglobin 73 g/L), and thrombocytopenia (54 × 10 9 /L). Prothrombin time and activated partial thromboplastin time were normal. Diagnoses: The patient was diagnosed as STAT5b-RARa-positive APL based on the clinical and laboratory findings. Interventions: ATRA was used immediately for induction treatment, then he was treated with ATRA + arsenic trioxide and got the severe cardiac insufficiency. Subsequently, consolidation chemotherapy was added with ATRA + Huangdai tablets + idarubicin and decitabine, cytarabine, aclamycin (DCAG). Outcomes: The patient relapsed soon after his first molecular complete remission (CRm), fortunately, he got a second CRm with DCAG. He has survived for more than 9 months and remains CRm, now he is looking for a suitable donor to prepare for hematopoietic stem cell transplantation (HSCT). Lessons: APL patients with STAT5B-RARa is not only resistant to ATRA, but also to conventional combination chemotherapy such as daunorubicin and cytarabine/idarubicin and cytarabine or other regimens. Relapse and extramedullary infiltration is common, HSCT is a effective treatment, and the best time for HSCT is after the first CR. It should be noted that this patient got CRm with DCAG after relapse, so the role of decitabine in APL with STAT5B-RARa needs to be considered.